A critical glocalization approach: attending to power in the innovation space. Issue 2 (2nd April 2020) - Wathen, Maria V.
ABSTRACT: The purpose of this paper is to provide community practitioners with the theoretical background to recognize and work in the interplay of global and local forces. This paper reviews globalization as a contested term and presents several globalization paradigms. It introduces critical glocalization as a guiding approach that sensitizes social workers to power dynamics. With this approach, social workers are encouraged to look for innovations that arise in the glocal sphere. They will understand the broader political, economic, structural, policy, and discursive contexts in which they are working, and intentionally look for the marginalized voices in our complex, interconnected world.